Analysing people's movement in the built environment via space syntax, objective tracking and gaze data - Eloy, S. (2022)
In this paper we use analysis tools from Space Syntax and objective observation of the human behaviour, to understand the impact of landmarks in the walking patterns of users of spaces. Our case study was a large exterior public open space (University Campus), in which participants could walk freely and simultaneously be tracked by several sensors. We carried Space Syntax analysis for this space, and then collected Global Positioning System (GPS) tracking information and used a mobile eye-tracking device to acquire eye gaze information. The collected data allowed us to map and analyse each subject behaviour in the public space. A more specific analysis was done to four selected landmarks that, according to the Space Syntax analysis, were the ones with higher integration values. Results indicate that landmarks with such higher integration values show also a larger count of fixations and saccades of gaze interaction.